A 13-year cohort study of musculoskeletal disorders treated in an autoplant, on-site physiotherapy clinic. - Sadi J; MacDermid JC; Chesworth B; Birmingham T (Journal of Occupational Rehabilitation, 2007)
Introduction The purpose of this study was to describe the rate and distribution of treatment visits provided in an on-site, automotive plant, physiotherapy clinic over a 13-year period. Method A retrospective cohort study was conducted using data collected at an on-site physiotherapy clinic (1990-2002, 65,977 visits; n = 2,636 workers). Results The average age of workers was 43 ± 9 years; most remained at work (85%) when treated. Disorders most commonly affected the shoulder, lumbar, and cervical regions; the median number of visits for these was 7, 6, and 5, respectively. Elbow disorders occurred commonly only for work-related complaints and required a median of eight visits. Rate of utilization was higher for women, with 47% of the plant's female workers attending physiotherapy in 1 year. Women had higher rates of cervical spine (12 vs. 22%) and wrist (5 vs. 10%) disorders. The two most common causes of injury reported by workers with an industrial injury were 'frank injury arising out of normal employment' (51%) and 'gradual onset/no frank injury' (37%). The diagnosis most often reported by the physiotherapist after initial assessment was 'strain' which was similar for both industrial (43%) and non-industrial (49%) injuries. The six main departments in this automotive plant account for 93% of all industrial injuries reported. Final Assembly accounted for the largest number and highest rate of injury, although shift variability was noted in utilization rates (13 vs. 26%), despite the same tasks, shift schedules, and demographics. Although there was no control group, the number of visits to discharge was lower than reported in the literature for off-site physical therapy; there was a large reduction in claims (441-275) following introduction of the clinic and reduced duration/costs of lost time were identified by the employer as a rationale to continue and enhance the service over time. Conclusions On-site physiotherapy services can provide early, cost-effective management of WRMSD in the automotive sector. Service utilization reflects the influence of gender, job task, and shift-dynamics on rates and location of WRMSD.